Using Young Tongue-Holding Forceps for Third Molar Autotransplantation as a New Method for Tooth Handling: A Case Report with a 1-Year Follow-Up - Shakerin, Hadi; Sadeghi, Mohammad Reza; Toumaj, Ahmad; Jafary Nodoushan , Zahra (Galen Medical Journal, 2025)
For the first time in autotransplantation literature, all extraoral procedures on the donor tooth were carried out while holding it by a Young Tongue Holding Forceps, potentially reducing damage to the PDL and enhancing the handling of the tooth. In this case report, we present the autotransplantation of a mandibular third molar into the socket of the adjacent second molar in an 18-year-old patient. The clinical and radiographic evaluation revealed severe pain and a periapical lesion from the previous root canal treatment. The surgical and endodontic steps were carried out with a focus on maintaining the viability of periodontal ligament cells, which would improve the overall prognosis of the transplantation. The donor tooth was secured in the ideal position using sutures for two weeks. The transplanted tooth was followed up for 12 months postoperatively, showing optimal healing and maturation of periodontal and periapical tissues. It seems that Young Tongue Forceps could be used in other dental practices that involve ex vivo or extraoral procedures on a tooth. Furthermore, the forceps could be modified and manufactured to accommodate every type of tooth.